Bystanders' reactions to intimate partner violence: an experimental approach. Issue 1 (1st January 2020) - Pagliaro, Stefano; Pacilli, Maria Giuseppina; Baldry, Anna Costanza
ABSTRACT: Intimate Partner Violence (IPV) is a widespread phenomenon. Despite the prevalence of IPV in Western societies, most cases remain unnoticed or at least unreported to authorities. Social psychologists have been investigating bystanders' reactions to IPV, to understand which factors may influence the willingness to intervene in support of a female victim of violence. We review a research programme that directly investigated personal and situational factors that make potential bystanders believe a woman victim of IPV deserves and needs (their) help and support, and what, on the contrary, makes them deny any such willingness to help. We present evidence about the situational antecedents of bystander's reaction, the underlying mechanisms of this intervention, and an extension of such evidence to non-prototypical cases, i.e., to an IPV episode occurring within a same-sex couple. We conclude by discussing future directions, and by highlighting the theoretical and practical contributions of this programme of research to the understanding of IPV for both researchers and practitioners.